Pan-Cancer Single-Cell Analysis Reveals the Core Factors and Pathway in Specific Cancer Stem Cells of Upper Gastrointestinal Cancer - Li, Leijie; Zhang, Yujia; Ren, Yongyong; Cheng, Zhiwei; Zhang, Yuening; Wang, Xinbo; Zhao, Hongyu; Lu, Hui (Frontiers in Bioengineering and Biotechnology, 2022)
Upper gastrointestinal cancer (UGIC) is an aggressive carcinoma with increasing incidence and poor outcomes worldwide. Here, we collected 39,057 cells and they were annotated into 9 cell types. By clustering cancer stem cells (CSCs), we discovered a ubiquitous existence sub-cluster CSCs in all UGICs which is named Upper gastrointestinal cancer stem cells (UGCSCs). The identification of UGCSCs function is coincident with the carcinogen of UGICs. We compared UGCSCs expression profile with 215,291 single cells from 6 other cancers and discovered that UGCSCs are specific tumor stem cells in UGIC. Exploration of the expression network indicated that inflammatory genes (CXCL8, CXCL3, PIGR, and RNASE1) and Wnt pathway genes (GAST, REG1A, TFF3, and ZG16B) are upregulated in tumor stem cells of UGICs. These results suggest a new mechanism for carcinogenesis in UGIC: mucosa damage and repair caused by poor eating habit leads to chronic inflammation, and the persistent chronic inflammation trigger Wnt pathway, ultimately this process induces UGICs. These findings establish the core signal pathway that connects poor eating habit and UGIC. Our system provides deeper insights into UGIC carcinogen and a platform to promote gastrointestinal cancers diagnosis and therapy.